Nonlinear analysis of reinforced concrete shells and the compressive membrane action on bridge deck slabs - Beatriz da Costa Fernandes; Jordlly Reydson de Barros Silva; Bernardo Horowitz (Revista IBRACON de Estruturas e Materiais)
Abstract There are reinforced concrete problems where it is essential to analyze the reinforcement stresses at the crack, such as verifying the Fatigue Limit State in bridge deck slabs and crack opening in water tanks. In view of this, this work presents a numerical model called Cracked Shell Model (CSM), which enables the determination of stresses in the orthogonal reinforcement of concrete shell elements. The CSM uses the layered method, where the thickness of the shell element is discretized into concrete layers subjected to a plane stress state. The reinforcements are evaluated using the Cracked Membrane Model (CMM), which considers the compression softening of concrete and the tension stiffening effects via the Tension Chord Model (TCM). The validation of the CSM was carried out with experimental and numerical shell data available in the literature. It has been shown to be capable of predicting the complete behavior of reinforced concrete shell elements, with good accuracy and low computational cost. Additionally, a study was conducted on the Compressive Membrane Action (CMA) on bridge deck slabs, which tends to increase the load capacity of these slabs. With this study it can be observed that the CSM, despite the good performance presented in the validation phase, as it is based on Kirchhoff thin plate theory (usual practice in many projects) failed to capture this effect, underestimating the ultimate load by an average of 44% in relation to experimental tests. This article aims to contribute to developing numerical models of reinforced concrete shells, in problems where the maximum reinforcement stress is essential.